England's Rise to Greatness, 1660-1763 - Baxter, Stephen (Clark Library Professorship, UCLA Series., 2021)
In 1660 England was already prosperous, free, civilized, and the possessor of the makings of an empire. In the century to follow, the island nation became the world's greatest power. This cohesive collection of essays on a wide range of topics illuminates important facets of the political history of England from the Restoration to the American War of Independence. Arthur J. Slavin of the university of Louisville discusses and important problem in legal history.